2014
DOI: 10.1007/s00432-014-1624-4
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol plays dual roles in pancreatic cancer cells

Abstract: Resveratrol plays dual roles in pancreatic cancer: as a tumor suppressor via the up-regulation of Bax; as a tumor activator via the up-regulation of VEGF-B; and the anticancer effect of RSV is much stronger than the cancer promotion effect. The combination of RSV with pharmacological inhibitor of VEGF-B might, therefore, be a promising modality for clinical pancreatic cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…Total RNA was isolated from equal number of islets using Trizol reagent (Takara Bio, Inc.) as described previously [20]. In brief, for cDNA synthesis 1.0 lg RNA was used, and reactions were carried out using the reverse transcription system (Promega, Shanghai).…”
Section: Quantitative Real-time Pcr (Qpcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated from equal number of islets using Trizol reagent (Takara Bio, Inc.) as described previously [20]. In brief, for cDNA synthesis 1.0 lg RNA was used, and reactions were carried out using the reverse transcription system (Promega, Shanghai).…”
Section: Quantitative Real-time Pcr (Qpcr)mentioning
confidence: 99%
“…Western blot analysis was performed as described previously [20]. In brief, cells were lysed and incubated for 30 min in ice-cold RIPA buffer.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Furthermore, we examined the protein level of GSK-3β, which has been reported as a down-stream molecule of VEGF-B in our previous study [21]. GSK-3β served as a tumor activator in pancreatic cancer, and phosphorylation at Ser 9 reduced the activity of this kinase [26].…”
Section: Resultsmentioning
confidence: 99%
“…RSV is shown to prevent a variety of cancers; including hepatocellular carcinoma [15], non-small cell lung adenocarcinoma [16], oral carcinoma [17], osteosarcomas [18], as well as PaCa [19, 20]. Interestingly, in previous study, we found that RSV played dual roles in PaCa cells, namely as a tumor suppressor via the promotion of apoptosis; as a tumor activator via the up-regulation of VEGF-B; and the anti-cancer effect of RSV was much stronger than the cancer promotion effect [21]. Therefore, we assumed that combination of RSV with pharmacological inhibitor of VEGF-B signaling pathway could potentiate the anti-tumor effect of RSV, and would be a promising modality for clinical PaCa therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol has a dual role in pancreatic cancer cells: on one hand, it acts as a tumor suppressor by accelerating apoptosis; on the other hand, it promotes tumorigenesis by up-regulating the expression of VEGF-B, which then activates GSK-3β and inhibits apoptosis [20]. Metformin suppresses resveratrol-induced expression of VEGF-B, thereby potentiating the anti-cancer effect of resveratrol via inhibition of VEGF-B/GSK-3β signaling pathway [19].…”
Section: Classic Anti-cancer Mechanisms Of Metforminmentioning
confidence: 99%